The Relationship Between Physical Activity and Cognition in Children: A Meta-Analysis - Sibley, A.; Etnier, J. L. (Pediatric Exercise Science, 2003)
The purpose of this study was to quantitatively combine and examine the results of studies pertaining to physical activity and cognition in children. Studies meeting the inclusion criteria were coded based on design and descriptive characteristics, subject characteristics, activity characteristics, and cognitive assessment method. Effect sizes (ESs) were calculated for each study and an overall ES and average ESs relative to moderator variables were then calculated. ESs (n = 125) from 44 studies were included in the analysis. The overall ES was 0.32 (SD = 0.27), which was significantly different from zero. Significant moderator variables included publication status, subject age, and type of cognitive assessment. As a result of this statistical review of the literature, it is concluded that there is a significant positive relationship between physical activity and cognitive functioning in children.